Why STEM? To sustain life. Ideas shared by Yayo Herrero at the first Escola d'Estiu d’EduglobalSTEM - Oriol Guinart Berrueco (Ciències, 2020)
One of the debates usually forgotten in education is that of the intentionality, that it, the aims of education. From our point of view, the aim of education for global and environmental justice, and for social transformation, must be central to the whole curriculum, including the STEM subjects. One of the most interesting current views to do so is provided by the ecofeminism approach, which entangles social ecologism and feminism. At the second session of the first summer school that the teachers’ group EduglobalSTEM organized, we enjoyed the reflections shared by Yayo Herrero. This article describes these reflexions and experiences resulting from that event.